‘People Don’t See You if You’re a Woman and You’re Not Really Dressed Up’: Visibility and Risk - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
Against a backdrop of research suggesting that young women are still expected to engage in active risk management on a night out (Brooks, ‘Guys! Stop doing it!’: Young women’s adoption and rejection of safety advice when socializing in bars, pubs and clubs. British Journal of Criminology, 51(4), pp. 635–651, 2011), this chapter will explore the centrality of understanding of space and visibility to young women’s negotiations of risk and safety in mainstream bars and clubs in Newcastle’s NTE. Visibility comes into play in two distinct ways here—firstly, as in the previous chapter, participants drew on narratives of ‘fitting in’, this time to describe the types of venues that felt comfortable and safe to them. Attending a venue where they felt out of place or ‘different’ to other patrons could leave women feeling exposed, visible and vulnerable, and these spaces were positioned as risky and dangerous. Secondly, women recognised that bars and clubs are spaces where ‘everyday’ experiences of heterosexualised violence are trivialised and normalised, and they managed their dress and appearance in particular ways in order to position themselves as less visible—or even invisible—to try to avoid ‘unwanted attention’ and harassment.
Keywords: Charvis; Posh People; Sexual Abuse Rape; Unwanted Attention; Working-class College Students